基于语料库的汉韩“重/轻”与“무겁다/가볍다”形名搭配语义范畴对比研究 - Kanghoon, Lim (Journal of Maobi, 2025)
This study focuses on the adjective pairs “Zhong/Qing” in Chinese and “Mugubda/Gabyubda” in Korean, aiming to compare their adjective-noun collocational patterns based on corpus data. Starting from their basic meanings, this paper analyzes sentence structures in which these adjectives appear either as predicates or attributives. Through large-scale corpus extraction, the study categorizes the semantic extensions and syntactic functions of these collocations. Additionally, the study integrates second language acquisition theories to observe error patterns among Chinese and Korean language learners. The findings reveal notable semantic discrepancies and usage divergences between the two languages, offering valuable insights for cross-linguistic teaching and learning.